Evaluation of Haematuria and Use of Phase Contrast Microscope: A Short Review - Sultana, T; Sultana, T; Rahman, MQ; Ahmed, ANN (Journal of Dhaka Medical College, 2011)
For centuries physicians have been using urine as one of the non-invasive means for assessing diseases. Haematuria is a frequently encountered abnormality in clinical practice. Haematuria may have either a glomerular or a non-glomerular origin. The morphological study of urinary red cells by Phase-Contrast Microscopy (PCM) is a useful diagnostic marker for glomerular bleeding, if correctly interpreted and used. Today, urinalysis and in particular identification of red cells morphology by Phase-Contrast Microscopy has been a widely accepted technique for determining the site of haematuria. A short review on haematuria and Phase-Contrast Microscopy are presented here for updating knowledge and academic interest. Key words: Phase-contrast microscope; Haematuria; Dysmorphic red cell. DOI: http://dx.doi.org/10.3329/jdmc.v20i1.8584 J Dhaka Med Coll. 2011; 20(1) :63-67